2015
DOI: 10.3390/s16010035
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Operating Parameters on Measurements of Biochemical Oxygen Demand Using a Mediatorless Microbial Fuel Cell Biosensor

Abstract: The conventional Biochemical Oxygen Demand (BOD) method takes five days to analyze samples. A microbial fuel cell (MFC) may be an alternate tool for rapid BOD determination in water. However, a MFC biosensor for continuous BOD measurements of water samples is still unavailable. In this study, a MFC biosensor inoculated with known mixed cultures was used to determine the BOD concentration. Effects of important parameters on establishing a calibration curve between the BOD concentration and output signal from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 28 publications
1
20
1
Order By: Relevance
“…The optimal pH and temperature for Cr(VI) removal by using O. anthropi observed in this study were consistent with those reported by Sultan and Hasnain (2012) [ 32 ]. Electrolytes, such as Na + and Cl − , exist at a high concentration in wastewater and can potentially affect the activity of microbes and the function of ion-exchange membranes in MFCs [ 23 ]. Thus, the effect of NaCl on the Cr(VI) removal efficiency of O. anthropi YC152 was investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal pH and temperature for Cr(VI) removal by using O. anthropi observed in this study were consistent with those reported by Sultan and Hasnain (2012) [ 32 ]. Electrolytes, such as Na + and Cl − , exist at a high concentration in wastewater and can potentially affect the activity of microbes and the function of ion-exchange membranes in MFCs [ 23 ]. Thus, the effect of NaCl on the Cr(VI) removal efficiency of O. anthropi YC152 was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…The protons transfer to the cathode compartment [ 21 ]. In addition, MFCs can produce a signal for practical applications such as powering electronic sensors to analyze pollutants and monitoring state variables for system control [ 22 , 23 ]. At present, MFC biosensors are applied to detect biochemical oxygen demand (BOD), toxicity, (volatile fatty acid) VFA, and Nickel (Ni) in wastewater and are validated to minimize the time and the cost [ 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Distributed sensors have been proven successful for the measurement of oxygen flows and concentrations. For example, Hsieh, Cheng, Liu, and Chung () studied a microbial fuel cell (MFC) biosensor inoculated with known mixed cultures to determine the biological oxygen demand (BOD) concentration. Their results indicated that monosaccharides were a good fuel for electricity generation by the MFC and that the developed MFC biosensor has great potential as an alternative BOD‐sensing device for online measurements of wastewater BOD.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a study focusing on the effects of operating parameters, where a MFC-based biosensor was inoculated with known mixed cultures to determine the BOD concentration, the results showed that methionine, phenylalanine, and ethanol were poor fuels for electricity generation, whereas monosaccharides gave good results [ 88 ]. Ji et al [ 89 ] found that electrical signal feedback was more sensitive than pH in the integrated MFC-UASB system, and that limits of sensitivity ranged from 3 × 10 −5 V (mg L −1 ) −1 to 8 × 10 −5 V (mg L −1 ) −1 for different concentration ranges.…”
Section: The Performance Of Mfc-based Biosensorsmentioning
confidence: 99%